(3GdJcja GdehQah(B-(3hXjaj dOi dGYHj cQI GdbOe HESJYeGd GdGdYGH GdeUZQI (B: (3OQGSI ejOGfjI YQVjI YfO GhGSW GcGOjejI ChdeHjc eGQSjdjG (B- (3aFI Gbd ef (B15 (3SfI s - (3YQbhH , MSGfs; (3JhGZRjJ, SgjdIs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3aj GdHOGjI GSJgddfG eTQhY HMKfG HJhRjY GSJHjGf NGU HGdOQGSI GdGSJWdGYjI Ydi eNJda GdeOQHjf hGdeMVQjf GdHOfjjf Phj GdeSJhi GdYGdj dQjGVI cQI GdbOe deMGhdI age GdXGgQI GdeQGO OQGSJgG, hGSJfJLfG ef NdGd GdaQR Cf Gdbdjd abW jSJYed WQjbI GdJOQjH GdHOfj GdeOeL (B((3GSJYeGd GdCdYGH GdeUZQI(B) (3eY Cf gPg GdWQjbI CNPJ eYGjjQ heMcGJ YGdejI ZjQ CfgG egeTI Ch eLghdI aj HdGOfG(B. (3ef NdGd gPG GdefHQ Sfbhe HGbJQGM HQfGeL JOQjHj eOeL NGU HGSJYeGd GdCdYGH GdeUZQI dQDjI eaYhdgG Ch JCKjQgG Ydi GdMGdI GdehQah(B- (3hXjajI YfO QjGVjj cQI GdbOe, MjK SfYed HHWGQjI GNJHGQGJ NGUI HGdbjGSGJ GdCfKQhHheJQjI hHYV GdUaGJ GdHOfjI (B((3GdbhI, GdSQYI, GdeOGheI(B) (3cd OhQI JOQjHjI eJhSWI (B((3JbQjHG cd TgQjf(B) (3deQGbHI Ch eJGHYI JCKjQ gPG GdHQfGeL WhGd GdehSe GdQjGVj(B. s
(3OcJhQGIs
Keywords: (3GdGdYGH GdeUZQIs; (3GdJMVjQ GdHOfj GdQjGVjs; (3GdJcja GdehQah(B-(3hXjajs; (3cQI GdbOes